Gender Predliction and Confunding Factors Affecting Pre Hospital Delay Among Acute Myocardial Infraction Patients. - Jayesh Sharma; Avanish kumar Bhardwaj (Asian Journal of Medical Research, 2020)
Background: Acute Myocardial Infarction (AMI) is a serious and life-threatening manifestation of coronary artery disease (CAD) affecting both males and females, which need immediate management. The present study was aimed to assess the gender difference and factors affecting pre-hospital delay among patients with AMI.Subjects and Methods:The 291 patients admitted with AMI from01-01-2018 to 31-12-2018 were studied. A descriptive comparative design was adopted for the study. Socio personal and clinical variables of the subjects were assessed. Pre-hospital delay was measured in terms of time from the onset of symptoms till the patient reaches a health care setting. One hour after the onset of symptom of AMI was considered as the Golden hour. Data was analyzed using SPSS 20.0 software.Results:Out of the 291 patients with AMI (146 males and 145 females), only 32.4% of males and 24.1% of females reached a health care setting within 1 hr of onset of symptoms. 35.2% of male patients and 43.5% of female patients reached the health care setting only after 6 hrs of onset of symptoms. Among the male patients, pre hospital delay was significantly associated with place of onset of symptoms (p<0.05), presence of someone with the patient at the time of onset of symptoms (p<0.05), and perception of symptoms developed, as an emergency (P<0.001). Whereas in female patients, significant association was observed in pre hospital delay with age of the patient (p<0.05), nature of the first symptom experienced (P<0.05) and perception of symptoms developed as an emergency (p<0.001).Conclusion: Our study shows the existence of pre hospital delay among patients with AMI in both males and females. The factors affecting pre hospital delay vary between males & females.